The Constitution - Prolman, Marilyn (Chicago Children Press, 1995)
Describes the need for unification in a growing country and discusses the problems and decisions of the men who drafted the Constitution of the United States
Includes index
Originally published: The story of the Constitution. Chicago : Children Press, 1969
11
Keywords: Constitutional history -- United States -- Juvenile literature; Constitutional history -- United States; Constitutional law -- United States -- Juvenile literature; Constitutions -- United States